New natural fibre reinforced aluminium composite for automotive brake pad - Maleque, Md. Abdul; Afdzaluddin, Atiqah; Ria Jaafar, Talib; Halim, Zahurin (Universiti Malaya, 2012)
The aim of this paper is to develop new natural fibre reinforced aluminium composite for automotive brake pad application. Four different laboratory formulations were prepared with varying coconut fibre contents from 0, 5, 10 and 15 volume fraction along with binder, friction modifiers, abrasive material and solid lubricant using powder metallurgy technique for the development of new natural fibre reinforced aluminium composites. The properties examined are density, porosity, microstructural analysis, hardness and mechanical properties using densometer, SEM, hardness tester and universal testing machine. The better properties in terms of higher density, lower porosity and higher compressive strength were obtained from 5 and 10% coconut fiber composites. The microstructure reveals uniform distribution of resin and coconut fibre in the matrix. It can be concluded that 5 and 10% showed better physico-mechanical properties compared to other formulations. Hence, natural coconut fibre is a potential candidate fiber or filler material for the automotive brake pad material.